1989
DOI: 10.1016/0035-9203(89)90401-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B surface antigen in pregnant mothers and its perinatal transmission

Abstract: 1000 pairs of maternal and cord blood samples were collected simultaneously at the time of delivery. 23 (2.3%) of the maternal samples were positive for HBsAg by enzyme-linked immunosorbent assay. HBeAg was detected in 11 (47%) of the 23 HBsAg positive mothers and anti-HBeAg was detected in another 5 samples. HBsAg and HBeAg were detected in 7 (30%) of the 23 cord blood samples from HBsAg-positive mothers, and anti-HBeAg was detected in one of these samples. At follow-up (6-18 months), antigenaemia had persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
4
26
0
Order By: Relevance
“…Without prophylaxis, a very large proportion of infants born to HBV positive carrier mothers may become carriers of HBV [30,31] . Infection in this high risk setting is prevented most effectively by prenatal screening to identify carrier mothers [32,33] , with administration of hepatitis B immunoglobulin at birth along with a course of vaccines to achieve both immediate and long lasting immunity to HBV. Many countries such as India lack the resources to implement such programs and must depend on vaccine alone to prevent the development of chronic HBV carriage in these babies.…”
Section: Discussionmentioning
confidence: 99%
“…Without prophylaxis, a very large proportion of infants born to HBV positive carrier mothers may become carriers of HBV [30,31] . Infection in this high risk setting is prevented most effectively by prenatal screening to identify carrier mothers [32,33] , with administration of hepatitis B immunoglobulin at birth along with a course of vaccines to achieve both immediate and long lasting immunity to HBV. Many countries such as India lack the resources to implement such programs and must depend on vaccine alone to prevent the development of chronic HBV carriage in these babies.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] A large study involving 8575 pregnant women from Northern India, documented HBsAg carrier rate in antenatal mothers to be 3.7%, HBeAg carrier rate 7.8% and vertical transmission was observed in 18.6%. 53 However, a recent study by Dwivedi et al 54 has shown a lower prevalence rate of 0.9%.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Figure 3b demonstrates [68]. Developing refers to data from developing countries which are not in east Asia or sub-Saharan Africa (this term is also used in Tables 2-4) and includes 2 studies from India [69,70], and 1 each from Egypt [71], Indonesia [72] and Kuwait [73]. [68], and Japan [76].…”
Section: Modelling Hbv Infection Patternsmentioning
confidence: 99%
“…[68], and Japan [76]. Developing includes 2 studies from India [69,70], and 1 each from Egypt [71] and Kuwait [73].…”
Section: Modelling Hbv Infection Patternsmentioning
confidence: 99%